1976
DOI: 10.1289/ehp.7613111
|View full text |Cite
|
Sign up to set email alerts
|

Methodological approaches to the study of the combined effect of atmospheric pollutants as illustrated by chlorinated hydrocarbons.

Abstract: The combined effect of substances with a unidirectional toxic action was studied with the use of several chlorinated hydrocarbons, including 1,2-dichloropropane, 1,2,3-trichloropropane, and perchlorethylene at various concentrations. The results of the study can be used as the basis for the development of methodological approaches to the study of the combined action of toxic substances administered by inhalation. The research plan also incorporated the problem of explaining the nature of the action of the mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The Soviet side studied the combined effect of several chlorinated hydrocarbons in mice and rats. They have found that the effects of the action of the mixtures of these gases at high and low concentrations do not differ, and the magnitude of the combined effect is the sum of the effect of the gases separately (15,16).…”
Section: Problem Area 2 Development Of Methods For Predicting the Biomentioning
confidence: 99%
“…The Soviet side studied the combined effect of several chlorinated hydrocarbons in mice and rats. They have found that the effects of the action of the mixtures of these gases at high and low concentrations do not differ, and the magnitude of the combined effect is the sum of the effect of the gases separately (15,16).…”
Section: Problem Area 2 Development Of Methods For Predicting the Biomentioning
confidence: 99%
“…The IARC designated 1,2-DCP as a group 1 carcinogen in 2014 13 ) . In animals, 1,2-DCP causes neurological complications (lethargy, CNS depression, and decreased activity) 14 , 15 ) . CNS overexposure (ingestion or inhalation) caused dizziness, disorientation, and coma in humans exposed to 1,2-DCP by accident or when attempting suicide 2 , 16 ) .…”
Section: Introductionmentioning
confidence: 99%